Polarity-dependent chemical characteristics of water-soluble organic matter from laboratory-generated biomass-burning revealed by 1-octanol-water partitioning - Lee, Wen-Chien (2021)
Polarity distribution of water-soluble organic matter (WSOM) is an important factor in determining the hygroscopic and cloud nucleation abilities of organic aerosol particles. We applied a novel framework to quantitatively classify WSOM based on the 1-octanol-water partition coefficient (KOW), which often serves as a proxy of polarity. In this study, WSOM was generated in a laboratory biomass-burning experiment by smoldering of Indonesian peat and vegetation samples. The fractionated WSOM was analyzed using a UV-visible spectrophotometer, spectrofluorometer, and time-of-flight aerosol chemical speciation monitor. Several deconvolution methods, including positive matrix factorization, parallel factor analysis, and least-squares analysis, were applied to the measured spectra, resulting in three classes of WSOM. The highly polar fraction of WSOM, which predominantly exists in the range of log KOW < 0, is highly oxygenated and exhibits similar optical properties as those of light-absorbing humic-like substances (HULIS, termed after the humic substances due to the similarity in chemical characteristics). WSOM in the least-polar fraction, which mainly distributes in log KOW > 1, mostly consists of hydrocarbon-like and high molecular weight species. In between the most- and least-polar fraction, WSOM in the marginally polar fraction likely contains aromatic compounds. The analyses have also suggested the existence of HULIS with different polarities. Comparison with previous studies indicates that only WSOM in the highly polar fraction (log KOW < 0) likely contributes to water uptake.